Designing A Self Oscillating Fet Mixer (SOM) - Patrick Lee, Voon Boke (Universiti Sains Malaysia, 2006)
To accomplish the project in designing a Self Oscillating FET Mixer (SOM), the main problem faced is to obtain the exact Intermediate Frequency (IF) at the desired frequency after implement the simulated circuit into printed circuit board (PCB). Besides of that, conversion gain obtains from the circuit after implemented into printed circuit board is less than the value obtains from simulation result. This project is done by design and simulates the circuit using HP-ADS (HP-Advanced Design system). After desired simulation result is obtained, the simulation circuit is implemented into FR4 type of PCB. Then, conversion gain, port-to-port isolation, and linearity issue is analyzed using spectrum analyzer. This result is then compared with the result from simulation using ADS, all problems arise from the design and analyzation will be considered and the inaccurate result from measurement will be discussed. The SOM designed is down conversion system. This circuit is designed using FR4 PCB board and surface mount component that helps in small in size and cost effective that applicable with the practical usage. Therefore, the design of this mixer and the analyzation can be make without any intricacy. Hopefully the design of this self oscillating FET mixer (SOM) can be continued and improved for the usage in variety of application in the future.